KAJIAN EFEKTIFITAS POLA SIRKULASI KAWASAN WISATA DESA TRADISONAL PENGLIPURAN - SURYADARMAWAN, I GUSTI AGUNG GDE; PRAGANINGRUM, TJOKORDA ISTRI; GIRI, I KETUT SUDIPTA; HERMAWAN, I PUTU YANA; SARI, PUTRI AGUNG PERMATA (Universitas Mahasaraswati K. Mataram, 2024)
Bali, as one of the main tourist destinations in Indonesia, has a variety of attractions, including the Penglipuran Traditional Tourism Village in Bangli Regency. The popularity of this tourist village has led to a significant increase in vehicle flow, especially on weekends and holidays, resulting in congestion around tourist areas. Vehicles parked carelessly on the side of the road interfere with mobility for both locals and other tourists. This study aims to evaluate the effectiveness of current circulation patterns and identify potential solutions. Using a qualitative method with a naturalistic approach, this study will observe and analyze vehicle movement patterns, parking behavior, and their impact on traffic and visitor comfort. The results of this study are expected to provide recommendations for more effective circulation pattern arrangement, including parking management, alternative routes, and road infrastructure improvements. With the implementation of the right solutions, it is hoped that the comfort and experience of tourists in the Penglipuran Traditional Tourism Village can be significantly improved, while maintaining smooth traffic for local residents.